Karakteristik distribusi horizontal parameter fisika-kimia perairan permukaan di pesisir bagian timur Balikpapan: The characteristic of horizontal distributio to the physical-chemical parameter of surface waters in the eastern site of Balikpapan coastal area - Aditya Irawan; Lily Inderia Sari (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
The research aimed to know the characteristic of horizontal distribution to the Physical-Chemical parameters of surface water in Eastern Site of Balikpapan coastal area. Result of research indicate that current pattern that happened tend to make a move northerly during the year to South. Hoizontal Distribution and temperature and TSS tend to increase to come near coast, while dissolved oxygen and salinity tend to increase while turbidity, conductivity, pH, phosphate and ammonia tend to flatten from coast till 4 mile to the sea. Horizontal Distribution Cu (0,001 - 0,014 mg / l) tend to increase to come near coast, Hg content tend to smaller 0,0005 mg / l and still under standard of sea water quality. Bottom of the eastern site of Balikpapan coastal tend to flat.